2007
DOI: 10.1111/j.1532-5415.2007.01569.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cost‐Effectiveness of a Behavior Intervention with Caregivers of Patients with Alzheimer's Disease

Abstract: Objectives-To examine the cost-effectiveness of a randomized, clinical trial of a home-based intervention for caregivers of people with dementia. Setting-Community-dwelling dementia caregiving dyads from the Memphis REACH II site. Design-This Participants-OfMemphis' random sample of 55 intervention and 57 control black and white dyads, 46 in each arm completed without death or discontinuation. Family caregivers were aged 21 and older, lived with the care recipient, and had provided 4 or more hours of care per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 51 publications
1
106
0
1
Order By: Relevance
“…They found significant reduction in hours of care (primary outcome) provided by the caregiver and concluded that the intervention was also cost-effective [84].…”
Section: Combination Of Individual and Group Based Multicomponent Intmentioning
confidence: 99%
“…They found significant reduction in hours of care (primary outcome) provided by the caregiver and concluded that the intervention was also cost-effective [84].…”
Section: Combination Of Individual and Group Based Multicomponent Intmentioning
confidence: 99%
“…physical and psychological impairments, impacting less on the healthcare system from an economic or a social perspective [15,16]. Literature reviews and meta-analyses confirm the association between greater mental burden and poorer physical and mental well-being: the responsibilities and the stressful experiences related to the caregiving role can cause depression, anxiety, worry and loneliness [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 92%
“…Considerando a diversidade etnica, cuidadores hispânicos e caucasianos, participantes das intervenções, experimentaram melhora significativa na qualidade de vida do que aqueles do grupo controle; sugerindo que a depressão clínica foi menor entre os cuidadores do grupo de intervenção (Belle, Burgio, Burns, Coon, Czaja, Gallagher-Thompson, Gitlin, Klinger, Koepke, Lee, Martindale-Adams, Nichols, Schulz, Stahl, Stevens, Winter & Zhang, 2006) Os custos emocionais e físicos da prestação de cuidados nos casos de demência são relevantes e a intervenção se mostra capaz de amenizar esses custos emocionais e físicos (Nichols, Chang, Lummus, Burns, Martindale-Adams, Graney, Coon & Czaja, 2008). Essas intervenções centram-se em fornecer ao cuidador informações sobre a enfermidade de seus pacientes, psicoeducação, aconselhamento psicológico ou mesmo acompanhamento psicoterápico breve (Glueckauf et al, 2012;Cheng et al,2012;Blom et al, 2013), das opções de psicoterapia breve, a que se destaca na literatura como alternativa de controle de estresse também nesses casos é a Terapia Cognitivo Comportamental (TCC) (Cheng et.…”
Section: Estudos De Intervençãounclassified